Geobiology of the late Paleoproterozoic Duck Creek Formation, Western Australia - Wilson, J.; Fischer, W.; Johnston, D.; Knoll, A.; Grotzinger, J.; Walter, M.; McNaughton, Neal; Simon, M.; Abelson, J.; Schrag, D.; Summons, R.; Allwood, A.; et al. (Elsevier Science BV, 2010)
The ca. 1.8 Ga Duck Creek Formation, Western Australia, preserves 1000 m of carbonates and minor iron formation that accumulated along a late Paleoproterozoic ocean margin. Two upward-deepening stratigraphic packages are preserved, each characterized by peritidal precipitates at the base and iron formation and carbonate turbidites in its upper part. Consistent with recent studies of Neoarchean basins, carbon isotope ratios of Duck Creek carbonates show no evidence for a strong isotopic depth gradient, but carbonate minerals in iron formations can be markedly depleted in C-13. In contrast, oxygen isotopes covary strongly with depth; delta O-18 values as positive as 2%. VPDB in peritidal facies systematically decline to values of 6 to 16% in basinal rocks, reflecting, we posit, the timing of diagenetic closure. The Duck Creek Formation contains microfossils similar to those of the Gunflint Formation, Canada; they are restricted to early diagenetic cherts developed in basinal facies, strengthening the hypothesis that such fossils capture communities driven by iron metabolism. Indeed, X-ray diffraction data indicate that the Duck Creek basin was ferruginous throughout its history. The persistence of ferruginous waters and iron formation deposition in Western Australia for at least several tens of millions of years after the transition to sulfidic conditions in Laurentia suggests that the late Paleoproterozoic expansion of sulfidic subsurface waters was globally asynchronous.